THE PERFORMANCE OF THE UNIVERSAL HEALTH SYSTEM (SUS) IN THE PHILANTHROPIC INSTITUTION LEAGUE AGAINST CANCER AT THE DR. LUIZ ANTÔNIO HOSPITAL, A REFERENCE IN CANCER TREATMENT IN NATAL/RN (REMUNOM, 2025)
This study aimed to analyze the challenges faced by the Unified Health System (SUS) in providing care to cancer patients at the philanthropic Dr. Luiz Antônio Hospital, maintained by the Liga Contra o Câncer, in Natal/RN, Brazil. Using a qualitative approach based on bibliographic review, document analysis, and direct observation, the research identified significant obstacles related to underfunding, limitations in human and structural resources, bureaucratic regulatory processes, and fragmented coordination among governmental levels. Although philanthropic, the institution provides essential public services, serving primarily SUS patients and facing constant pressure to maintain efficiency and quality in a highly complex context. The analysis also revealed the Liga’s efforts to implement humanization strategies, professional training, and infrastructure expansion, positioning itself as a regional reference in oncological care. It is concluded that to ensure the sustainability of cancer care in philanthropic institutions, it is necessary to strengthen integrated management, revise funding mechanisms, and improve coordination among government levels.Keywords: Philanthropy; Healthcare Management; Liga Contra o Câncer (League Against Cancer); Oncology; SUS (Brazil’s Unified Health System).